Integrated Pest Control in Forestry - Mathur, R. N. (Indian Forester, 1977)
The forester is faced continually with insect problems at every stage of the growth of the tree. On an average the insects cause a loss of roughly Rs. 100 per annum per square mile over workable forests and this gives the total loss caused by forest insects as Rs. 125 lakhs. Before undertaking control of the pest, one should know the ecology and dynamics of the insect populations. The control methods adopted are too varied, or sometimes limited in application. Modern insecticides create in due course new complications, Some important and major examples are cited to illustrate the integrated control measures adopted in India.